Crystal structure across the β to α phase transition in thermoelectric Cu2–xSe - Eikeland, Espen; Blichfeld, Anders B.; Borup, Kasper A.; Zhao, Kunpeng; Overgaard, Jacob; Shi, Xun; Chen, Lidong; Iversen, Bo B. (IUCrJ, 2017)
Here, the crystal structure uniquely imparts the specific properties of a material, and thus provides the starting point for any quantitative understanding of thermoelectric properties. Cu2–xSe is an intensely studied high performing, non-toxic and cheap thermoelectric material, and here for the first time, the average structure of β-Cu2–xSe is reported based on analysis of multi-temperature single-crystal X-ray diffraction data. It consists of Se–Cu layers with additional copper between every alternate layer. The structural changes during the peculiar zT enhancing phase transition mainly consist of changes in the inter-layer distance coupled with subtle Cu migration. Just prior to the transition the structure exhibits strong negative thermal expansion due to the reordering of Cu atoms, when approached from low temperatures. The phase transition is fully reversible and group–subgroup symmetry relations are derived that relate the low-temperature β-phase to the high-temperature α-phase. Weak superstructure reflections are observed and a possible Cu ordering is proposed. The structural rearrangement may have a significant impact on the band structure and the Cu rearrangement may also be linked to an entropy increase. Both factors potentially contribute to the extraordinary zT enhancement across the phase transition.